The Western Amazonian Boundary for Avifauna Determined by Species Distribution Patterns and Geographical and Ecological Features - Nores, Manuel (International Journal of Ecology, 2011)
In northern South America, an extensive tropical lowland runs 5,000 km from the Atlantic coast to the foot of the Andes. The slope is gentle until about 500 m where the eastern Andes rise abruptly. The lowland supports Amazonia, which is the most extensive tract of tropical rainforest on the planet. Most of its boundaries are well defined, but the boundary between Amazonia and the forest of the eastern slopes of the Andes has not been clearly defined. To determine for avifauna whether Amazonia is restricted to the lowland of northern South America or whether it also extends up into the eastern slopes of the Andes, different types of data were used. The results indicate that Amazonia may be restricted to the lowland that extends from the Atlantic coast to the foot of the Andes, up to about 500 m. Consequently, the number of bird species strictly endemic to Amazonia would be 290. Comparison with the distribution of vegetation on the eastern slopes of the Andes also suggests that Amazonia as a biome may be restricted to the lowland that extends from the Atlantic coast to the foot of the Andes, up to about 500 m.